Different geospatial information behaviors of new domestic and international graduate students. Issue 1 (24th February 2016) - Oh, Chi Young; Butler, Brian S.
ABSTRACT: This paper presents the findings from an online survey investigating how new students seek geospatial information in an unfamiliar environment. By surveying 149 new graduate students at University of Maryland, College Park, this study identifies the geospatial information needs and information sources used during their adjustment in new environments, and examines the factors that may affect different geospatial information behaviors (GIBs) of new students, such as populousness of students' countries of origin on campus, gender, age, and program level (Master's, PhD). Findings include (1) international students' greater emphases on survival‐related geospatial information; (2) gender differences in the importance of navigational and transportation information and frequency of using navigational information sources during adjustment; (3) significant differences among socio‐national and demographic groups for geospatial information needs and for the use of information sources. The findings are discussed in ways to further our understanding of new students' GIB in unfamiliar environments and inform further research in human information behavior.